Comparative efficacy of different herbal and modern anthelmintics against gastrointestinal nematodiasis in fowl - Alam, Md.; Alam, Khondoker; Begum, Nurjahan; Amin, Mohammad (International Journal of Biological Research, 2014)
The aqueous and ethanol extract of some plants and plant materials were screened for their in vitro anthelmintic effects against gastrointestinal nematodes of fowl were studied. The plant materials were extracted in distilled water (aqueous extract) and ethyl alcohol (ethanol extract). Screening of freshly prepared aqueous extract of three plant materials namely neem (Azadirachta indica), papaya (Carica papaya), korolla (Momordica charantia) and two patent drugs Eskanex® (Levamisole) and Eskapar® (Piperazine) were selected. Aqueous extracts of 25mg/ml, 50mg/ml and 100mg/ml concentration; ethanol extracts of 10mg/ml, 25mg/ml, and 50mg/ml were used for screening. Among the selected plants and patent drugs and all three concentration of aqueous extracts papaya seed was found best at 25mg/ml concentration (41%), 50mg/ml concentration (74%) and 100mg/ml (92%) followed by korolla (22%, 70% and 90% in 25mg/ml, 50mg/ml and 100mg/ml concentration respectively) against adult parasite and these plants namely papaya seed showed significant efficacy against infective larvae L3. Ethanol extracts of plants also showed significant efficacy against adult gastrointestinal worms at a concentration of 50 mg/ml. Among the selected plants and all three concentration of the ethanol extract revealed the highest efficacious plant (100%) at a concentration of 50 mg/ml. In all concentrations of ethanol extract papaya was observed as the best plant (100%, 98% and 84% at 50mg/ml, 25mg/ml and 10mg/ml concentration respectively) followed by korolla (100%, 93% and 74% at 50mg/ml, 25mg/ml and 10mg/ml concentration respectively) against adult whereas in case of larvae it showed significant efficacy. The present study suggests that papaya, korolla and neem are effective and can be used against the treatment of nematodiasis in fowl in alternative of patent drugs. More studies are needed to determine the active principles of pharmacological and toxicological assessment. Keywords: Comparative Efficacy, Extract, Gastrointestinal, Herbal Anthelmintic, Nematodiasis.